2006
DOI: 10.1136/gut.2005.070417
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus core protein promotes proliferation of human hepatoma cells through enhancement of transforming growth factor   expression via activation of nuclear factor- B

Abstract: Background: Hepatitis C virus (HCV) infection is a major cause of human hepatocellular carcinoma (HCC). The precise mechanism of hepatocarcinogenesis in humans by HCV is currently unclear. It was recently shown, however, that transgenic mice with the HCV core gene often develop HCC, suggesting tumorigenic activity of the HCV core protein. Further, the HCV core protein expressed in HepG2 cells transfected with the core gene was shown to stimulate proliferation of transfectants through activation of nuclear fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 33 publications
3
50
0
2
Order By: Relevance
“…Previous reports indicated that ROS induced by the structural core protein has an antiapoptotic and proliferative effect on hepatocytes (48,56,57). Hepatocytes expressing the core protein alone were reported to induce TGF-␤ and connective tissue growth factor mRNA (59).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicated that ROS induced by the structural core protein has an antiapoptotic and proliferative effect on hepatocytes (48,56,57). Hepatocytes expressing the core protein alone were reported to induce TGF-␤ and connective tissue growth factor mRNA (59).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of transforming growth factor-a, an EGFR ligand, can be induced by hepatitis viral proteins and may act synergistically with viral infection in hepatocarcinogenesis [362][363][364]. Results of EGFR expression in HCC tumor tissues, mainly by immunohistochemistry, varied in different studies [365], and activating mutation of EGFR, the major determinant of efficacy of EGFR inhibitors in lung cancer [366], was rarely found in HCC tumor tissue [367].…”
Section: Anti-egfr Mttmentioning
confidence: 99%
“…There are two different mechanisms of NF-kB activation by HCV. One is induced by HCV core protein which can bind to the death domain of TNF receptor 1 (TNFR1) and to the cytoplasmic domain of the LTb receptor (LTbR) to activate NF-kB (Tai et al, 2000;Sato et al, 2006). HCV can also promote proliferation of human hepatoma cells by activation of the ERK MAP kinase pathway through upregulation of TGFa transcription through activation of NF-kB.…”
Section: Helicobacter Liver Infection and Nf-jb Signalingmentioning
confidence: 99%
“…The HCV core protein can promote proliferation of human hepatoma cells by activating NF-kB, thereby leading to TGF-a induction and activation of the ERK/ MAP kinase pathway (Sato et al, 2006). The region of the core protein responsible for NF-kB activation encompasses amino acids 9-11 which are highly conserved (93%) in all HCV strains (Mann et al, 2006).…”
Section: Chronic Hepatitis Cmentioning
confidence: 99%